Tweet it! ESL writing activity module using Twitter / Nurshahirah Azman and Zaemah Abd Kadir - Azman, Nurshahirah; Abd Kadir, Zaemah (2021)
There is a demand to transform the whole teaching and learning experience in accommodating the needs of the students from the younger generation who are more familiar with the advanced technology in the present days. When it comes to learning English as a second language, many would find learning it in a common classroom setting with a fixed syllabus to be challenging and less effective as there is a tendency to make the learning process an isolated experience from the real world. With the utilisation of one of the popular social networking sites, Twitter, the learning of English writing could be transformed into a more interactive and relatable one to these young generations. Twitter has a lot of facilitative features for engaging interactions among users, along with simplicity as its main highlight of the site. Available on both the website and mobile application, engaging with students through Twitter would only require simple steps into the application to begin with. The 'TWEET IT!' highlights the need to improve ESL learners' ability to improve their argumentative skills, This is a crucial element in writing as the 'TWEET IT!' ESL Writing Activity module provides a guideline to use Twitter for ESL writing activity, with 14 argumentative topics from easy to advance level. These topics are comprised of general knowledge, current issues, and relevant discussion prompts. The module aims for a duration of 14 weeks (one semester), which is suitable for the target ESL learners in higher learning institutions. By fully utilising this module, it is expected that ESL learners would be able to improve their argumentative skills, enhance their vocabulary skills as well as increase their confidence to interact with others using the English language correctly.